(untitled) (ModaPalavra e-periódico, 2020)
The parade of samba schools in Rio de Janeiro is a seasonal and thematic party that is performed by several professionals linked to the creation of services and products, depending on the party. In this article we analyze issues in the creative process of the designer Severo Luzardo, when designing a costume. Thus, we intend to emphasize the relations between carnival and design, inserting the carnival practice as a "particular form of design". For this we present a carnival costume inspired by corn and the co nsequent materialization of this project (from the sketch to the fantasy - ready prototype), weaving parallels with the methodological processes of fashion design and product design. We intend to discover practices that reveal us design processes and that le ad us to approach the carnival to the academic practice of design.